Serum Bovine Immunoglobulin for Chemotherapy-Induced Gastrointestinal Mucositis. (May 2018) - Arikapudi, Sowminya; Rashid, Saima; Al Almomani, Laith Adel; Treece, Jennifer; Baumrucker, Steven J.
Cancer treatments including chemotherapy and radiotherapy treat cancer by targeting rapidly dividing cells. Although these forms of treatment damage rapidly dividing cancer cells, they are also toxic to the cells of the gastrointestinal tract, leading to inflammation of the mucosal layer (mucositis) and causing nausea, vomiting, diarrhea, and abdominal pain. Improvement in symptoms may allow patients to have better performance status permitting ongoing treatment and possibly a better prognosis. This article describes the pathophysiology of chemotherapy-induced mucositis and includes 3 case reports of treatment of mucositis with serum bovine immunoglobulin.